“TOAST” CONSEPT IN DIFFERENT LANGUAGE SYSTEM - Azizova Moxinur Muzaffarjon kizi (Galaxy International Interdisciplinary Research Journal, 2022)
In this article we research the concept “toast”, etymology of the word. In different languages system we study the word “toast” meaning, expression, variety of toast in different culture, in dialects, the most famous toasts in history from well-known authors, poets, philosophers, and playwrights.